St. Peter and st. Paul’s Church in Vilnius: a study in meta-codal symbolism of Christian architecture - Oržikauskas, Gytis (Journal of Architecture and Urbanism, 2014)
The paper examines Christian architecture from the perspective of “meta-codal function”, i.e. through examination of architectural symbolism expressed solely by architectural means. Emphasizing symbolic and semantic content of architecture, the paper offers a broader research field of architectural artistry by using a wider iconographic comparison. As a representative of baroque architecture and the most prominent example of architectural symbolism, St. Peter and St. Paul’s Church in Vilnius (1668–1702) has been selected for the research. The iconographic programme of this church is compared to most distinct iconographic themes identified through the analysis of some examples of historic Christian architecture. By this method, the research detaches from the usual stylistic analysis and poses the most basic question in architectural artistry: is architecture capable of expressing the independent artistic content which can translate more than architecture’s general appearance.